1988
DOI: 10.1111/j.1432-1033.1988.tb13736.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the cellulolytic system of Trichoderma reesei QM 9414

Abstract: Limited action of papain on the native forms of two cellobiohydrolases (CBH) from Trichoderma reesei (CBH I, 65 kDa, and CBH II,58 kDa) leads to the isolation of the respective core fragments (56 kDa and 45 kDa) which are fully active on small, soluble substrates, but have a strongly reduced activity (respectively 10% and 50% of the initial value) on microcrystalline cellulose (Avicel).By partial sequencing at the C terminus of the CBH I core and at the N terminus of the CBH I1 core the papain cleavage sites h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
286
1
3

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 540 publications
(313 citation statements)
references
References 29 publications
23
286
1
3
Order By: Relevance
“…The specific activities of the six major enzymes obtained, the two cellobiohydrolases CBH1 (Cel7a) and CBH2 (Cel6a), the major two endoglucanases EG1 (Cel7b) and EG2 (Cel5a), as well as the xyloglucanase Cel74a and the xylanase XYN1, were measured on Avicel, carboxymethylcellulose (CMC), xylan and xyloglucan (Table 1). The two cellobiohydrolases have high activity on Avicel cellulose, consistent with values found in the literature [20,21] whereas endoglucanases and XYN1 show lower activities. A low activity of xylanase on Avicel and CMC has been reported previously [22].…”
Section: Resultssupporting
confidence: 90%
“…The specific activities of the six major enzymes obtained, the two cellobiohydrolases CBH1 (Cel7a) and CBH2 (Cel6a), the major two endoglucanases EG1 (Cel7b) and EG2 (Cel5a), as well as the xyloglucanase Cel74a and the xylanase XYN1, were measured on Avicel, carboxymethylcellulose (CMC), xylan and xyloglucan (Table 1). The two cellobiohydrolases have high activity on Avicel cellulose, consistent with values found in the literature [20,21] whereas endoglucanases and XYN1 show lower activities. A low activity of xylanase on Avicel and CMC has been reported previously [22].…”
Section: Resultssupporting
confidence: 90%
“…The rate constants for CBH1 and CBH2 (k CBH1 and k CBH2 ) were used based on the best fit to the data from the experimental data. The specific activity of CBH2 was twice that of CBH1 (Tomme et al, 1988). The rate constant for EG1, k EG1 , was set at fivefold that used for CBH1 in light of the relative specific activity of these two enzymes, mechanistic considerations, and experimental data fitting (Tomme et al, 1988;Zhang and Lynd, 2004).…”
Section: Parameter Valuesmentioning
confidence: 99%
“…The specific activity of CBH2 was twice that of CBH1 (Tomme et al, 1988). The rate constant for EG1, k EG1 , was set at fivefold that used for CBH1 in light of the relative specific activity of these two enzymes, mechanistic considerations, and experimental data fitting (Tomme et al, 1988;Zhang and Lynd, 2004). The typical composition of unfractionated T. reesei cellulase mixtures was taken to be as reported elsewhere (Goyal et al, 1991) such that 100 mg cellulase contains 60 mg CBH1, 20 mg CBH2, and 12 mg EG1.…”
Section: Parameter Valuesmentioning
confidence: 99%
“…It has also been shown that deletion of the CBH 1 gene has a drastic effect on the cellulolysis of T. reesei [3]. Most fungal cellulases have a common structural organization where the main part of the enzyme, the catalytic core, is connected through a heavily glycosylated linker region to a small cellulose-binding domain (CBD) [4]. This gives the whole molecule an elongated tadpole shape (180 A in the case of CBH 1) [5].…”
Section: Introductionmentioning
confidence: 99%